Perbandingan Kepekaan Tempo Peserta Didik Perdesaan dan Perkotaan melalui Body Percussion - Rizal Ridwan Suhendar; Resa Respati; Aini Loita (JURNAL ARMADA PENDIDIKAN, 2025)
This study aims to analyze differences in tempo sensitivity among elementary school students in rural and urban areas using the Carl Orff approach through body percussion techniques. Tempo sensitivity is a vital component in music education that supports the development of motor coordination, concentration, and structured thinking. The research employed a comparative experimental method without a control group, involving 44 fifth-grade students from both rural and urban settings. Data were collected using musical skill tests and analyzed through normality and Mann-Whitney tests. The results indicate a significant difference between the rural and urban student groups (significance value 0.009 < 0.05), suggesting that socio-cultural environments influence the development of tempo sensitivity. Urban students demonstrated higher tempo awareness, possibly due to greater exposure to music and popular culture, while rural students faced limitations in musical resources and expressive freedom. These findings highlight the importance of culturally responsive pedagogical approaches in elementary music education.